2011
DOI: 10.1007/s10847-011-0018-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of inclusion complex of vitamin E compound with 2,6-di-O-methylated β-cyclodextrin as the solubility enhancer and its kinetic determination for radical scavenging ability

Abstract: The structure of the inclusion complex of a-tocopherol (vitamin E compound) with 2,6-di-O-methylated b-cyclodextrin (DM-b-CD) was characterized by 2D ROESY NMR measurements, suggesting that DM-b-CD includes the side-chain moiety of a-tocopherol. The inclusion complexation of DM-b-CD showed the usefulness of water solubilizer for the radical scavenging assay of vitamin E compounds in aqueous solution. Using the electron paramagnetic resonance (EPR) competitive spin trapping method, we determined the oxygen radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Vitamin E has a wide range of use as food supplements and in pharmaceuticals; however, its poor solubility is a drawback for its use and processing. Inclusion complexation with CD molecules enables to overcome this challenge and enhance the water solubility of Vitamin E compounds. Here, to show the fast dissolution of Vitamin E/HPβCD-IC NF and to show the enhanced water-solubility of Vitamin E in Vitamin E/HPβCD-IC NF, a piece of Vitamin E/HPβCD-IC NF web sample (approximately 4 cm × 4 cm) and a drop of pure Vitamin E (at the similar amount presence in the nanofiber) put into separate Petri-dishes and water was poured onto the samples. As apparent from Figure and the Movie S1, Vitamin E/HPβCD-IC NF web was dissolved immediately in water, whereas pure Vitamin E remained in the Petri dishes without dissolving.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin E has a wide range of use as food supplements and in pharmaceuticals; however, its poor solubility is a drawback for its use and processing. Inclusion complexation with CD molecules enables to overcome this challenge and enhance the water solubility of Vitamin E compounds. Here, to show the fast dissolution of Vitamin E/HPβCD-IC NF and to show the enhanced water-solubility of Vitamin E in Vitamin E/HPβCD-IC NF, a piece of Vitamin E/HPβCD-IC NF web sample (approximately 4 cm × 4 cm) and a drop of pure Vitamin E (at the similar amount presence in the nanofiber) put into separate Petri-dishes and water was poured onto the samples. As apparent from Figure and the Movie S1, Vitamin E/HPβCD-IC NF web was dissolved immediately in water, whereas pure Vitamin E remained in the Petri dishes without dissolving.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, CDs have drawn interest to parry the limitations of Vitamin E by inclusion complexation. As reported in the literature, CD-IC of Vitamin E can be utilized to enhance the solubility and oxidation stability of this active agent. Even in the related studies, which were performed by our group, CD-ICs of Vitamin E were incorporated into polymeric nanofibers such polylactic acid and polycaprolactone for potential applications in food packaging and wound healing, where we have achieved enhanced release and effective antioxidant profile along with the improved water-solubility and UV-light stability for Vitamin E.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, there has been a rising interest of using CDs in order to overcome limitations of antioxidants, antibacterials, drugs and provide advantages as mentioned above. The studies associated with IC of a-TC with CDs were reported in the literature as well to increase solubility [14,15] and improve oxidative stability of foods [16]. In addition to these studies, there are studies in which a-TC/CD-IC incorporated into polymeric films [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamins are essential micro-nutrients that the human body requires for the proper functioning of its metabolism (Kamal-Eldin and Appelqvist, 1996; Suarra et al , 1993; Suzuki et al , 1993). Among various vitamins, vitamin E (VE), which is obtained from many fruits and vegetables, nuts and seeds, and seed oils, is a strong and effective free radical scavenger to protect the body cells and bio-macromolecules from the radical attacks (Sueishi et al , 2012; Koontz et al , 2009). Hence, VE possesses many advantages like anti-aging, prevention and treatment of cardiovascular diseases and anti-tumor effect.…”
Section: Introductionmentioning
confidence: 99%